Research progress on clinical application of allergen immunotherapy in children - Zhang Pingping, Yang Lifen, Liang Ying, Li Yating (Xin yixue, 2022)
Allergen immunotherapy （AIT） is the only treatment to change the process of allergic diseases by inducing allergen-specific immunity tolerance. Although a large number of clinical trials and meta-analysis have confirmed the safety and effectiveness of AIT, it has not been widely applied. New allergen vaccines are constantly developed and better AIT treatment strategies are being explored worldwide. However, most of the clinical data are obtained from adults, and the pediatric data are lacking. It is urgent to promote the standardization of diagnosis and treatment and formulate a unified AIT strategy for pediatric allergic diseases. This article reviews the research progress on clinical application of AIT in children, aiming to provide reference for in-depth investigations.